Kinetics of Phenylhydrazine-Glucose Reaction In Anionic and Cationic Surfactant Media - Nagajyothi, K.; Raghwan, P.S.; Gopalan, R. (Asian Journal of Chemistry, 2010)
Osazone formation by glucose has been shown to occur at room temperature in the presence of surfactants. ·The kinetics of this reaction reveal that the rate is increased by both anionic and cationic swfactants at premicellar concentrations whereas it is retarded at postmicellar concentrations. Also, in the presence of surfactants, the reaction depends on the first order on phenylhydrazine but is zero order with respect to glucose. A mechanism involving adsorption of phenylhydrazine on surfactant as a slow step followed by a fast attack by glucose is proposed.